Low‐mode internal tides and balanced dynamics disentanglement in altimetric observations: Synergy with surface density observations. Issue 3 (16th March 2017) - Ponte, Aurélien L.; Klein, Patrice; Dunphy, Michael; Le Gentil, Sylvie
Abstract: The performance of a tentative method that disentangles the contributions of a low‐mode internal tide on sea level from that of the balanced mesoscale eddies is examined using an idealized high resolution numerical simulation. This disentanglement is essential for proper estimation from sea level of the ocean circulation related to balanced motions. The method relies on an independent observation of the sea surface water density whose variations are 1/dominated by the balanced dynamics and 2/correlate with variations of potential vorticity at depth for the chosen regime of surface‐intensified turbulence. The surface density therefore leads via potential vorticity inversion to an estimate of the balanced contribution to sea level fluctuations. The difference between instantaneous sea level (presumably observed with altimetry) and the balanced estimate compares moderately well with the contribution from the low‐mode tide. Application to realistic configurations remains to be tested. These results aim at motivating further developments of reconstruction methods of the ocean dynamics based on potential vorticity dynamics arguments. In that context, they are particularly relevant for the upcoming wide‐swath high resolution altimetric missions (SWOT). Key Points: Mesoscale and submesoscale may have a signature on sea surface density Low‐mode internal tides have a weaker signature on sea surface density Sea surface density may help identify low‐mode internal tide signatures in altimetric data